The face of Ivan Machabel in the memoirs of contemporaries - Marjanishvili, Mariam (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2019)
Many myths and legends are connected with the disappearance of the great translator of the great Shakespeare, Ivan Machabel. This process continues today. Researchers still provide materials based on assumptions or versions that rely less on documentary research and reality. Many memories of the strange death or disappearance of Ivan Machabel are also scattered abroad, the authors of which are his contemporaries, his direct eyewitnesses, and give us many references that shed new light on the face of the immortal ancestor, the many mysterious aspects of his life and work. The story of Rezo Gabashvili, the son of writer Ekaterine Gabashvili, a worthy representative of Georgian political emigration, attracts attention from several memoirs. Among the memoirs are also many interesting places gathered to immortalize the public work of his wife, Anastasia (Tasso) Machabel, and the creative activity of Ivan Machabel. Tasso Machabel’s authority and name grew when he began to publish the writings of his worthy wife, Ivan Machabel, and around this issue, Daraz ought to write about the writings of his late wife. Regarding the „Bankobiana“, which was unleashed between two great figures, the memoirs of Giorgi Zhuruli, a political emigrant, a National Democrat, and a member of the first coalition government of independent Georgia, draw attention: „Ilia was preparing for each session as a student for the exams. During the separation of technical and principled questions, he was often equipped with complete documentation, quoting from special books...“ The details of the memoirs clearly show the lines to create a portrait of Ivan Machabel, in which not only the translator of Shakespeare in the past and the personality of a prominent public figure live but also these icons bring to life the icon of a worthy patriot.